2012
DOI: 10.1038/nature11219
|View full text |Cite
|
Sign up to set email alerts
|

The molecular evolution of acquired resistance to targeted EGFR blockade in colorectal cancers

Abstract: Colorectal tumors that are wild-type (WT) for KRAS are often sensitive to EGFR blockade, but almost always develop resistance within several months of initiating therapy1,2. The mechanisms underlying this acquired resistance to anti-EGFR antibodies are largely unknown. This situation stands in marked contrast to that of small molecule targeted agents, such as inhibitors of ABL, EGFR, BRAF, and MEK, in which mutations in the genes encoding the protein targets render the tumors resistant to the effects of the dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

52
1,404
3
23

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,532 publications
(1,482 citation statements)
references
References 28 publications
52
1,404
3
23
Order By: Relevance
“…KRAS mutations were frequently detected in systemic metastatic cancers, and these were newly detected after acquired resistance to anti-EGFR antibody. Recently, mutation analysis using peripheral blood-socalled liquid biopsy-has been applied to colorectal cancer [9,10,[23][24][25]. In most published reports, quantitative PCR and BEAMing were used for detection with plasma DNA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…KRAS mutations were frequently detected in systemic metastatic cancers, and these were newly detected after acquired resistance to anti-EGFR antibody. Recently, mutation analysis using peripheral blood-socalled liquid biopsy-has been applied to colorectal cancer [9,10,[23][24][25]. In most published reports, quantitative PCR and BEAMing were used for detection with plasma DNA.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we confirmed that KRAS mutations were newly detected after acquired resistance to anti-EGFR antibody contained in chemotherapy, as other papers have reported. Since the first report of a patient with acquired resistance to cetuximab having newly detected KRAS mutation in cancer tissue, several papers have demonstrated acquired KRAS mutations, including mutations detected in plasma [8,10,11]. The mechanism of appearance of KRAS mutations after acquired resistance to anti-EGFR antibody has been assumed to be clonal selection from a minor population of pre-existing mutations or novel spontaneous mutations, but this mechanism has not been clarified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trois échantillons plasmatiques contenant un allèle KRas muté présentaient une discordance avec le profil de mutations de la tumeur du patient [20]. Des mutations de l'oncogène KRas indétectables dans les tissus tumoraux avaient également pu être mises en évidence à partir de sérum par dPCR BEAMing [30], illustrant la capacité des techniques de dPCR à reflé-ter l'hétérogénéité clonale de la tumeur. DOSSIER TECHNIQUE REVUES cellules tumorales à des molécules inhibitrices de l'EGFR (gefitinib et erlotinib, deux inhibiteurs sélectifs de la tyrosine kinase de EGFR), alors que la mutation T790M est identifiée comme une mutation secondaire de résistance à ces mêmes molécules.…”
Section: Trois Exemplesunclassified
“…Thus, from the beginning, the tumor contains cells harboring genetic lesions that can sustain resistance to targeted therapies. As mentioned by Dr. Vogelstein in a recent paper, "resistance is a fait accompli and the time to recurrence is simply the interval required for the subclone to repopulate the lesion" [8]. The presence of genetic heterogeneity in the primary tumor may also explain the common finding of patients presenting, at relapse, different metastases, each bearing a diverse genetic alteration responsible for drug resistance.…”
mentioning
confidence: 99%